2012
DOI: 10.1007/s00330-012-2419-0
|View full text |Cite
|
Sign up to set email alerts
|

MR T1ρ as an imaging biomarker for monitoring liver injury progression and regression: an experimental study in rats with carbon tetrachloride intoxication

Abstract: • MR T1ρ is a valuable imaging biomarker for liver injury/fibrosis. • Liver T1ρ was only mildly affected by oedema and acute inflammation. • Liver MR T1ρ decreased when liver fibrosis and injury regressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
3
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 46 publications
4
56
3
1
Order By: Relevance
“…How these processes contribute to the elevated T1rho measurement deserve careful investigation, which can be answered partially by careful animal model studies. In an imperfect rat study reported by us (21), it can be seen that acute edema of liver caused by CCl4 intoxication was not a dominant contributor of T1rho increase. After the withdrawal of CCl4 stimulus, it seems Letter to the Editor How liver pathologies contribute to T1rho contrast require more careful studies that the lowering of elevated liver T1rho was faster than the resolve of fiber tissue deposition in rat liver.…”
mentioning
confidence: 73%
“…How these processes contribute to the elevated T1rho measurement deserve careful investigation, which can be answered partially by careful animal model studies. In an imperfect rat study reported by us (21), it can be seen that acute edema of liver caused by CCl4 intoxication was not a dominant contributor of T1rho increase. After the withdrawal of CCl4 stimulus, it seems Letter to the Editor How liver pathologies contribute to T1rho contrast require more careful studies that the lowering of elevated liver T1rho was faster than the resolve of fiber tissue deposition in rat liver.…”
mentioning
confidence: 73%
“…A number of MR imaging techniques have been investigated to assess early liver parenchyma fibrosis, including T 1 rho imaging [2631], tagged MRI assessing liver strain [32], MR elastography [33, 34] and intravoxel incoherent motion (IVIM) technique [35, 36]. Our current study for the first time evaluated the feasibility of CEST imaging of in vivo liver at the clinical field strength of 3T, demonstrating the difference between over-night-fast and post-meal statuses.…”
Section: Discussionmentioning
confidence: 99%
“…In this study T2 relaxation's contamination to T1ρ elevation was not investigated, as it is known that rat BDL model is only associated with only mild inflammation in portal spaces (17,18,(26)(27)(28). In addition, previous study on CCl4 induced liver fibrosis model development demonstrated T2 and T1ρ follow different time courses; therefore T2 lengthening will not considerably contribute to T1ρ lengthening in this study (39). Another limitation is that only one liver fibrosis model is used in this study.…”
Section: Bdl Is a Well Established Model For Liver Fibrosis Researchmentioning
confidence: 92%